(untitled) (Journal of Engineering, 2011)
In this paper, the static analysis for finding the best location of boxes inside the composite wing-box structure has been performed. A software ANSYS (ver.11) was used to analyses the Aluminum wing to find the maximum stresses reached in. These results are used as a base for the composite wingbox to find the numbers of layers and location of the box beam and its dimensions so that the composite wingbox may carry the same loading conditions in the Aluminum wing. Analysis showed that a composite wingbox having two boxes is better than the single or triple boxes wing based on stress to weight ratio. Mass saving of (40%) had been achieved when composite wing-box is used instead of Aluminum wing.